Taxonomic revision of the southwestern Atlantic Madracis and the description of Madracis fragilis n. sp. (Scleractinia: Pocilloporidae), a new coral species from Brazil - Elizabeth Neves; Rodrigo Johnsson (Scientia Marina, 2009)
The genus Madracis has been known in Brazil from four deep water species, namely M. mirabilis, M. asperula, M. brueggemanni and M. pharensis, and one zooxanthellate species from shallow water environments, M. decactis. Delicate fragments of a small branching colony of an undescribed Madracis were collected at 73 m depth, northern Salvador (Bahia State). Although resembling the congeners M. asperula and M. brueggemanni, the new species has distinct features including reduced branch thickness, smaller diameter of corallite and columella structure and pattern of coenosteum ornamentation. Because of the worldwide focus on reef-building corals, knowledge of azooxanthellate scleractinians remains scarce. In addition to contributing to the inventory of Brazilian coral fauna, the occurrence of a new species of Madracis provides further evidence of the high diversity of deep-water coral communities in the tropical South Atlantic.